Anthropological characteristics of the Armenian highlands population and ethnogenetic situation in South Eastern Europe in the Middle Age - Khudaverdyan A.Yu.; Zhamkochyan А.S.; Hakopyan N.G.; Babayan F.S.; Engibaryan A.A.; Khachatryan А.А.; Eganyan L.G. (Вестник археологии, антропологии и этнографии, 2018)
The article presents preliminary results of an anthropological research of human bone remains, obtained during excavations of medieval monuments on the territory of the Republic of Armenia. Cases of deliberate artificial modifications of skulls and unintentional cradle deformations were observed. Two unusual shapes (triangular, circular) of gaskets on the occipital bone in the individuals with frontal-occipital deformation were found. An individual from Burakn with artificial modification of the skull is characterized by a static asymmetry of the skull, the facial skeleton and the dental system. Craniological data indicates a heterogeneous anthropological composition of the population. A specific set of characteristics close to the Caucasion type were present among the inhabitants of Hovhannavank in the Late Middle Age. Results of the intergroup statistical analysis identified close morphological affinities between the Middle Age skulls from Armenia with groups from Southern and North-Western Caucasus, Iran, Mesopotamia. This article also analyzes morphological features of the postcranial skeleton. Muscular relief оn bones was very well developed in the vast majority of cases.